DESIGN OF EXPERT SYSTEM BASED ON CERTAINTY FACTOR ALGORITHM IN DIAGNOSIS OF CHOLESTEROL LEVEL IN ADOLESCENTS - Dewi, Kumala; Kurniawan, Edi; Sudarmin, Sudarmin (Jurnal Teknik Informatika (Jutif), 2022)
An expert system is a system that seeks to adopt humans to computers. As for experts, this system can be used as an experienced assistant. People are susceptible to cholesterol starting from the age of 20 years. The public submits the cholesterol by consulting a doctor directly. If cholesterol levels are high, people will experience pain such as headaches, chest pain, and numbness in the arms, but this pain is not necessarily a symptom of rising cholesterol levels, it could be a symptom of other diseases such as fever, colds, fatigue. , and others. Cholesterol is a fat found in the bloodstream or body cells that is actually needed for the formation of cell walls and as a raw material for several hormones. Therefore, it is divided into Low Density Lipoprotein (LDL), High Density Lipoprotein (HDL) and Triglycerides. The method used is the Certainty Factor method, which is built using the PHP programming language, and the MYSQL DBMS. Certainty Factor is a measure of certainty to a fact or certainty. The certainty factor determines the size of a thing or certainty. The application of Certainty Factor is expected to make the expert system more accurate. The result of this research is an application that can later be used to assist the public in diagnosing cholesterol levels so that people do not need to go directly to the doctor